2021
DOI: 10.3389/fnut.2021.755883
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in the Relationship Between Gender and Deep Vein Thrombosis Among Stroke Patients

Abstract: Introduction: Accumulating evidence had demonstrated that females had a higher risk of deep vein thrombosis (DVT) than males, but the mechanism was still unknown. Vitamin D was found to play an essential role in DVT, and gender may influence the serum vitamin D levels. This study aimed to explore whether vitamin D played a role in the gender difference in DVT.Materials and Methods: A total of 444 patients with acute stroke were recruited, which were divided into the DVT group (n = 222) and the non-DVT group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Finally, thrombotic complications are common in such patients; vitamin D is also involved in the regulation of thrombotic pathways (31,32). The mechanisms through which Vitamin D may influence pro-thrombotic pathways is closely related to its anti-inflammatory properties, which reduce endothelial activation and oxidative stress (33). In our study, low vitamin D levels in COVID-19 patients were related to inflammatory, pro-thrombotic and metabolic markers of severity, confirming observations from previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, thrombotic complications are common in such patients; vitamin D is also involved in the regulation of thrombotic pathways (31,32). The mechanisms through which Vitamin D may influence pro-thrombotic pathways is closely related to its anti-inflammatory properties, which reduce endothelial activation and oxidative stress (33). In our study, low vitamin D levels in COVID-19 patients were related to inflammatory, pro-thrombotic and metabolic markers of severity, confirming observations from previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, thrombotic complications are common in such patients; vitamin D is also involved in the regulation of thrombotic pathways ( 31 , 32 ). The mechanisms through which Vitamin D may influence pro-thrombotic pathways is closely related to its anti-inflammatory properties, which reduce endothelial activation and oxidative stress ( 33 ). In our study, low vitamin D levels in COVID-19 patients were related to inflammatory, pro-thrombotic and metabolic markers of severity, confirming observations from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that age was not associated with proximal DVT occurrence, which is consistent with the findings of Nathan et al They found that age was not a risk factor for proximal thrombosis ( 18 ). Studies have shown that female sex is an independent risk factor for DVT ( 19 , 20 ). First, platelet reactivity is significantly higher in women than in men ( 21 ), and second, the common iliac vein (CIV) is more likely to be compressed in women ( 22 , 23 ), leading to a higher incidence of DVT.…”
Section: Discussionmentioning
confidence: 99%